Come wid ... - Intellectual Property Service Centre (Kingston, Jamaica : Lithographic Printers Limited.)
This poster done by the Intellectual Property Service Centre invites the general public to come with their original works to have their intellectual property rights protected.
Keywords: Copyright. -- Poster. -- Jamaica